A research update on correlates of heavy episodic drinking among undergraduate college students. - Montauti, Sara; Bulmer, Sandra Minor (American Journal of Health Education, 2014)
Despite prevention efforts of colleges and universities across the nation, there have been no substantial decreases in heavy episodic drinking among undergraduates over the past 2 decades.This study provides an update on correlates of heavy episodic drinking for a recent cohort of undergraduate college students.A cross-sectional survey design was utilized. Participants were randomly selected undergraduate students from a public 4-year university located in the Northeast.Heavy episodic drinking was associated with male gender, white race, having a family history of drug or alcohol abuse, smoking cigarettes, and using marijuana. Age, athlete status, completion of an alcohol education program, condom use, depression, anxiety, and financial stress were not associated. After controlling for gender and race, marijuana use and smoking cigarettes were found to increase predictability of heavy episodic drinking.Rates of heavy episodic drinking remain high but correlates may be shifting for this cohort of college students. Opportunities to address heavy episodic drinking concurrently with cigarette smoking and marijuana use should be explored.Qualitative research methods are needed to gain insight into reasons for heavy episodic drinking; information that could inform the creation of more effective programming. © 2014 Copyright © SHAPE America.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/027-307-320-726-457 tex.type: [object Object]
Keywords: dept.hhs

Using CBPR methods in college health research exploring excessive alcohol consumption - Bulmer, Sandra Minor; Barton, Barbara A; Liefeld, Julie; Montauti, Sara; Santos, Stephanie; Richard, Melissa; Hnath, Laura; Pelletier, Kara; Lalanne, Jude (Journal of Adolescent Research, 2016)
Community-based participatory research (CBPR) is a collaborative methodology that uniquely involves stakeholders in all stages of the research process. CBPR has been widely utilized in the field of public health, but not widely employed with college populations. This study utilized CBPR methods within a college community to gain insight into excessive alcohol consumption. Six student researchers planned and carried out a rigorous qualitative study at a public university in the Northeast region of the United States. A total of 48 undergraduate participants were recruited for focus groups that were facilitated by two student researchers, and transcribed and analyzed using thematic analysis methods. Students' reasons for drinking alcohol were focused within the themes of inclusion, habitual default, and the student development process. Social media, strict policy/enforcement, and student's desire to avoid responsibility led to increased risk and consequences related to drinking. Students recommended late night transportation and a Good Samaritan policy as strategies to improve student safety. This study led to student advocacy and policy change directed at improving student's health and safety and demonstrated that CBPR methods show promise for engaging students and producing meaningful data.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/015-321-517-465-575 tex.type: [object Object]
Keywords: college issues; dept.hhs; dept.mft; emerging adulthood; health; qualitative methods; substance use